Crude protein levels, productive performance and egg characteristics of second cycle layer hens - Sosa-Montes, Eliseo; Sánchez-Morales, Fernando; Pro-Martínez, Arturo; Martínez-Cruz, Elvia; Salinas-Jiménez, Luis Donaldo; González-Cerón, Fernando (Ecosistemas y Recursos Agropecuarios, 2021)
It was evaluated the effect of two commercial feeds (16 and 18%) with different crude protein (CP) content on the productive performance and egg characteristics of second-cycle hens. Each feed was randomly assigned to 210 hens that were housed two per cage. A 16 h light : 8 h dark regime was used. Daily ration of feed was 115 g bird-1. Egg production (PorP, %), egg weight (PesH, g), egg mass (MasH g bird-1 d-1), feed conversion (ConA g g-1), percentages of different egg categories and benefit cost ratio (B/C) were recorded during 52 days (d). Each d represented a replicate. During the last eight days, 64 eggs were randomly selected from each treatment (8 eggs d-1) to record in each egg: length (L, cm), width (A, cm), egg shape index (IFH), weight of yolk, white and shell (PesY, PesCla y PesCas, g, respectively) and their percentages (PorY, PorCla and PorCas, %, respectively). The 18% CP treatment produced better values (P < 0.05) of PorP, PesH, MasH, ConA, L and A than the 16% CP treatment. No effects (P > 0.05) were detected on the variables: IFH, PorY and B/C. Eggs from birds with 18% CP showed higher (P < 0.05) PorCla and lower PorCas than eggs from birds with 16% CP. In conclusion, the commercial feed with 18% CP improved productive performance and several egg characteristics, without affecting the benefit cost ratio.